2005
DOI: 10.1091/mbc.e04-05-0425
|View full text |Cite
|
Sign up to set email alerts
|

The Deubiquitinating Enzyme Ubp1 Affects Sorting of the ATP-binding Cassette-Transporter Ste6 in the Endocytic Pathway

Abstract: Deubiquitinating enzymes (Dubs) are potential regulators of ubiquitination-dependent processes. Here, we focus on a member of the yeast ubiquitin-specific processing protease (Ubp) family, the Ubp1 protein. We could show that Ubp1 exists in two forms: a longer membrane-anchored form (mUbp1) and a shorter soluble form (sUbp1) that seem to be independently expressed from the same gene. The membrane-associated mUbp1 variant could be localized to the endoplasmic reticulum (ER) membrane by sucrose density gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…Several components required for cell fusion have been identified in the yeast S. cerevisiae (summarized in White and Rose, 2001); however, whether these compounds cycle between endosomes and the plasma membrane remains to be elucidated. The yeast a-factor transporter Ste6 undergoes endocytic recycling (Kelm et al, 2004;Schmitz et al, 2005) and has additional roles in cellcell fusion (Elia and Marsh, 1996). Moreover, it was demonstrated that chitin synthases, which participate in wall formation, undergo endocytic recycling in S. cerevisiae (Ziman et al, 1996), and the same might hold true for U. maydis (U.…”
Section: Discussionmentioning
confidence: 98%
“…Several components required for cell fusion have been identified in the yeast S. cerevisiae (summarized in White and Rose, 2001); however, whether these compounds cycle between endosomes and the plasma membrane remains to be elucidated. The yeast a-factor transporter Ste6 undergoes endocytic recycling (Kelm et al, 2004;Schmitz et al, 2005) and has additional roles in cellcell fusion (Elia and Marsh, 1996). Moreover, it was demonstrated that chitin synthases, which participate in wall formation, undergo endocytic recycling in S. cerevisiae (Ziman et al, 1996), and the same might hold true for U. maydis (U.…”
Section: Discussionmentioning
confidence: 98%
“…This complex, comprised of Daxx, murine double minute 2 (MDM2), p53, and herpesvirus-associated ubiquitin-specific protease (HAUSP), has specificity and agility, quickly changing which components are ubiquitinated and which are deubiquitinated. The deubiquitinating enzymes in the cell have been shown to have an "editing" function that, by removing ubiquitin chains, spares proteins from proteasomal degradation and allows them to return to their normal cellular function (53)(54)(55). Non-canonical ubiquitin chain linkages that are resistant to proteasomal degradation are more susceptible to the action of deubiquitinases.…”
Section: Discussionmentioning
confidence: 99%
“…Ubp6p associates with the proteasome, where it removes ubiquitin from substrates before their degradation, allowing ubiquitin to be recycled (65,66). Ubp1p is thought to target an as yet unidentified component of the endocytic pathway, since overexpression of a soluble Ubp1p isoform stabilizes at least two cargo proteins of this pathway, Ste6p and Ste2p (67).…”
Section: Ubiquitination Of Atg19p May Be a Functionalmentioning
confidence: 99%